f(x) = 4(x − 6)2

x

f(x)

−1 196

0

1

2

3

f(-1)=4(-1-6)^2

-1= 4(-7)^2=-196

f(0)=4(0-6)^2=4(-6)^2=-144

f(1)=4(1-6)^2=4(-5)^2=-100

f(2)=4(2-6)^2=4(-4)^2=-64

f(3)=4(3-6)^2=4(-3)^2=-36

so filling in the table we get

-1 196

0 -144

1 -100

2 -64

3 -36

I hope this helps. Please best my answer! Thanks!

6

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up